ANALISIS WACANA KRITIS SIFAT KONSUMERISME DI BULAN RAMADAN PADA IKLAN MARJAN BUDOIN 2025 “CALON ARANG” - Fitra Rahmayufa Muhammad; Ageng Soeharno (MEDIAKOM, 2026)
The phenomenon of the commodification of religious and cultural values in Ramadan advertisements, particularly in the Marjan Budoin 2025 advertisement "Calon Arang," indicates a shift in the spiritual meaning of Ramadan toward excessive consumption practices. The advertisement not only presents products as a complement to the celebration, but also normalizes the consumption of branded products as a central part of celebrating the holy month. This study aims to analyze the image of consumption constructed in the Marjan Budoin 2025 advertisement and identify changes in the meaning of Ramadan worship that are shaped into a consumptive lifestyle through visual and narrative elements. This study uses a qualitative approach with Norman Fairclough's critical discourse analysis model. Data were collected through observation and documentation, validated through interviews with experts, and then analyzed based on three dimensions: text structure, discourse production practices, and socio-cultural practices. The results show that the advertisement frames consumption as a symbol of family happiness and emotional recovery, positions Marjan products as an image of spiritual well-being, and reinforces the norm of purchasing products during Ramadan celebrations. This condition indirectly places the value of simplicity as an aspect that is increasingly marginalized in popular culture.